Valorization of Carob and Brewer’s Spent Grain as Growth-Substrate Supplements in Tenebrio molitor Rearing - Irene Ferri; Matilda Rachele Dametti; Sara Frazzini; Matteo Dell’Anno; Luciana Rossi (Animals)
Background: Agro-industrial by-products, such as carob and brewer’s spent grain (BSG), have gained increasing attention as sustainable feed ingredients capable of enhancing the nutritional and functional value of Tenebrio molitor larvae. This study aimed to evaluate the effects of carob and BSG supplementation of growth substrates on larval performance and the functional properties of the resulting insect meals. Methods: Seven-week-old larvae were reared for 14 days on the following three diets: control (wheat bran), wheat bran + carob (Trt1), and wheat bran + BSG (Trt2). Larval weight, substrate consumption, and survival were recorded. After processing, insect meals were analyzed for chemical composition, total phenolic content (TPC), and antioxidant activity in both water- and lipid-soluble extracted fractions. Results: Both treatment groups showed significantly higher final weights than the control (Ctrl: 104.9 ± 2.69 g; Trt1: 114.8 ± 1.26 g; Trt2: 116.9 ± 1.07 g; p < 0.05). TPC was highest in the control for both fractions, and the antioxidant activity was similar between the Ctrl and Trt1 groups in the water-soluble fraction but significantly lower in the Trt2 group (p < 0.05). Conclusions: These findings highlight the potential of carob and BSG for sustainable insect farming, though their functional benefits may depend on the inclusion levels and their interaction with insect metabolism.